Increasing Student Studies Activity in Learned Mathematics by use of Concept Repeat at SDN 03 Kampung Jawa - Yeni Elmina (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This research intent to increase activity and Mathematics studying student result utilizes concept repeat at class VI SDN 03 Kampung Jawa. Base on the problem aught at the site bases writer observation be student struck a snag in understands concept, student visible confused given by study material a new one since student doesn’t control material earlier one. This research most turns in at class action research (classroom research) with 4 steps which is: Preparation (planning), learning performing (action), learning activity observation (observation), process evaluation and learning result (reflection). Executed research in 2 cycles. This research doing for student to class VI SDN 03 Kampung Jawa, Kota Solok which amount to 28 person and 1 person observer, during 2 months from March untul April 2015. Method that is utilized on this research is descriptive method. From the observational end product data that acquired that learning by use of concept repeat can be increase mathematics studying activity student class VI SDN 03 Kampung Jawa, Kota Solok.